2021
DOI: 10.21037/atm-21-3345
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the clinical presentations, progression, and sequela of pelvic inflammatory disease through physiological, histological and ultrastructural evaluation of a rat animal model

Abstract: Background: Patients with pelvic inflammatory disease (PID) are at an increased risk of ectopic pregnancy, infertility, and varying degrees of chronic pelvic pain. The aims of this study were to establish a rat model of PID and characterize its progression in order to assist in the study of pathophysiological mechanisms and to provide animal model for future studies of PID treatments.Methods: Fifty Sprague-Dawley rats (female, 6-weeks-old) were divided into a model group (n=28) and a control group (n=22). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…We also monitored white blood cell (WBC) counts in the blood, which is an indicator of infection-related inflammation. Previous study showed a temporary decrease in WBC in PID model group rats at the beginning of 0–2 days, which might be caused by the severe infection in PID rats ( Fan et al, 2021 ). The WBC count in the PID model group remained elevated until D7 and then began to decline, but it was still at a high level.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We also monitored white blood cell (WBC) counts in the blood, which is an indicator of infection-related inflammation. Previous study showed a temporary decrease in WBC in PID model group rats at the beginning of 0–2 days, which might be caused by the severe infection in PID rats ( Fan et al, 2021 ). The WBC count in the PID model group remained elevated until D7 and then began to decline, but it was still at a high level.…”
Section: Resultsmentioning
confidence: 93%
“…According to our previous study, PID model rats experience a 14- to 21-day period of acute inflammation, with the degree of inflammation being the highest at 6–8 days, followed by a period of chronic inflammation and sequelae with adhesion ( Fan et al, 2021 ). The day of model establishment was considered D-3, drug was administered from D0 to D14, and samples were collected on D3, D14, and D49 ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations